Research on the Existing Problems and Countermeasures of Chinese Film Derivatives Industry - He, Yushu (International Journal of Global Economics and Management, 2024)
Film derivatives, which is, products developed by using film elements and film culture. The box office revenue of American movies only accounts for less than 30% of the whole industry, and the remaining 70% are derivative industries. In China, the market development of film derivatives is still in its infancy and has great potential. By comparing and analyzing the present situation of film derivatives industry in China and the United States, this paper finds some problems existing in China's derivatives industry by using data analysis and specific case analysis, and thus puts forward some development strategies of domestic film derivatives market.